1996
DOI: 10.1080/00926239608405301
|View full text |Cite
|
Sign up to set email alerts
|

AIDS prevention in high-risk African American women: Behavioral, psychological, and gender issues

Abstract: A three-year longitudinal intervention study was implemented to reduce high-risk drug and sexual behaviors in methadone-dependent African American women. Participants were recruited from four inner-city methadone maintenance programs and randomly assigned either to an eight-week peer counseling and leadership training group or to a control group. The 107 trainees and 97 controls completed pretests and posttests at two, four, and seven months. This paper focuses on final data related to the subjects' sexual bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 28 publications
3
13
1
Order By: Relevance
“…Regarding the increased sexual risk behaviors of women, compared with men, prior studies have highlighted the challenges faced by HIV-positive women in convincing their male partners to use condoms. These challenges include not feeling confident about discussing condom use with their partners and not feeling confident about being able to disclose their HIV infection status to their partner [28][29][30]. Having depressive symptoms was also a significant factor for engaging in highrisk sexual behavior.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the increased sexual risk behaviors of women, compared with men, prior studies have highlighted the challenges faced by HIV-positive women in convincing their male partners to use condoms. These challenges include not feeling confident about discussing condom use with their partners and not feeling confident about being able to disclose their HIV infection status to their partner [28][29][30]. Having depressive symptoms was also a significant factor for engaging in highrisk sexual behavior.…”
Section: Discussionmentioning
confidence: 95%
“…A third explanation is that the effects of drug treatment on sexual risk reduction may have been moderated by gender. In this regard, Hetherington et al (1996) found that women in methadone maintenance felt powerless to actually achieve safer sex despite their perceived vulnerability to HIV. Other authors concluded that cultural and ethnic norms may circumscribe women's adoption of safer sexual behavior and that, thus, although they may want to have safer sex, women operate within gender role contexts that make it difficult (Grella et al, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Another review found modest reductions in risky sexual behavior for drug treatment-based HIV prevention programs (Prendergast, Urada, & Podus, 2001). Other studies suggest that the effects of drug treatment may differ by gender (Grella, Annon, & Anglin, 1995;Grella, Etheridge, Joshi, & Anglin, 2000;Hetherington, Harris, Bausell, Kavanagh, & Scott, 1996;Wells, Calsyn, Clark, Saxon, & Jackson, 1996). Furthermore, carefully conducted trials involving intensive long-term detoxification coupled with cognitive therapy (Sees et al, 2000), as well as community-based harm reduction strategies such as needle exchange and bleach distribution (Lurie & Reingold, 1993), have shown improvements in injection-related risk behavior but minimal or no impact on sexual risk practices.…”
Section: Introductionmentioning
confidence: 97%
“…Attention also must be paid to the influence of gender role socialization on prevention efforts. Research findings suggest that many African American women perceive themselves to be powerless over conditions that place them at risk such as multiple sex partners, incarcerated partners, and drug use (Battle, Cummings, Yamanda, & Krasnovsky, 1996;Harris & Kavanaugh, 1995;Hetherington, Harris, Bausell, Kavanaugh, & Scott, 1996). For example, Black women may consider themselves confrontational (with their sex partners) if they have to discuss previous sexual history, monogamy, condom use, and so on.…”
Section: Gender Roles Cultural Norms and Beliefsmentioning
confidence: 95%